Literature overview on the field of co-opetition - Stein, Harald D. (Business: Theory and Practice, 2010)
Co-opetition is a perspective on business relationships which highlights the ambivalence of competition and cooperation. Game theory is regarded as the mathematical tool for solving co-opetition related problems. The major step for introducing “co-opetition” into public discussion and economic research has been made by Brandenburger and Nalebuff in 1996. However they target a non-professional readership. A multitude of publications has followed, where the authors mostly focus on specific aspects of the problem and investigate particular industries. This paper gives a comprehensive literature overview on the field of co-opetition.